2018
DOI: 10.1088/1748-9326/aaec63
|View full text |Cite
|
Sign up to set email alerts
|

Reducing nitrogen footprints of consumer-level food loss and protein overconsumption in Japan, considering gender and age differences

Abstract: The agro-food system perturbs the nitrogen (N) cycle through its N loads to the environment. The present study focused on food-related consumer-level N loads in Japan from 1961-2015, with a particular focus on food loss and protein overconsumption. Gender and age differences were also analyzed. Consumer-level food loss was negligible until the 1970s, when it began to slowly increase, accounting for an average of 13.2% of the annual net supply during 2011-2015. Japanese people have consumed more protein than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The food N footprint of oil palm products calculated in the present study was compared with previously reported N footprints of several countries and the world average (Gu et al 2013, Pierer et al 2014, Shibata et al 2014, Stevens et al 2014, Liang et al 2016, Oita et al 2016, Hutton et al 2017, Shindo and Yanagawa 2017, Hayashi et al 2018 (table 3). The food N footprint of oil palm products in these countries ranged from 0.07 to 0.18 kg N capita -1 yr -1 , whereas their food N footprint ranged from 8.9 to 32 kg N capita -1 yr -1 .…”
Section: Food Nitrogen Footprint Of Oil Palm Productsmentioning
confidence: 87%
See 4 more Smart Citations
“…The food N footprint of oil palm products calculated in the present study was compared with previously reported N footprints of several countries and the world average (Gu et al 2013, Pierer et al 2014, Shibata et al 2014, Stevens et al 2014, Liang et al 2016, Oita et al 2016, Hutton et al 2017, Shindo and Yanagawa 2017, Hayashi et al 2018 (table 3). The food N footprint of oil palm products in these countries ranged from 0.07 to 0.18 kg N capita -1 yr -1 , whereas their food N footprint ranged from 8.9 to 32 kg N capita -1 yr -1 .…”
Section: Food Nitrogen Footprint Of Oil Palm Productsmentioning
confidence: 87%
“…In many cases, the N footprint is calculated on a national scale (e.g. Leach et al 2012, Shibata et al 2014, Hayashi et al 2018. The N-calculator method expresses the food N footprint of item i as:…”
Section: Calculation Of the N Footprintmentioning
confidence: 99%
See 3 more Smart Citations